TREND PEMOTONGAN DAN PRODUKSI DAGING TERNAK SAPI POTONG DI KABUPATEN BANYUMAS - Utari, Zea; Widiyanti, Rahayu; Hidayat, Nunung Noor (ANGON: Journal of Animal Science and Technology, 2022)
Background. Trend of Slaughter and Production of Beef Cattle in Banyumas Regency. The purpose of this research is to know the development of beef cattle population in Banyumas Regency, to know the trend of slaughtering beef cattle in Banyumas Regency from 2011 to 2020, to know the trend of beef production (supply) in Banyumas Regency for the last 10 years from 2011 to 2020. Material and Methods. The sampling method was carried out by taking data in Banyumas Regency through the Central Bureau of Statistics of Banyumas Regency and the Central Statistics Agency of Central Java Province. The data observed were the dependent variable in the form of population trend data (Y1) and beef beef production trend data (Y2) in Banyumas Regency and the independent variable in the form of year (X) for the last 10 years from 2011 to 2020. The data collected were analyzed using descriptive analysis and simple statistics to provide an overview of the number and average population and beef cattle production and the data were also analyzed using simple linear regression to determine the trend of production and population trends. Result. The results of the analysis of beef cattle population trends show the equation Y1 = 17779 -735.41x and (R2) is 0.6843. The value of the coefficient of determination (R2) is 0.6843, meaning that the variance of the dependent variable can be explained by the independent variable of 68.43% percent. The results of the analysis of meat production trends show the equation Y1 = 4,976,301.07 - 285,084.61x and (R2) is 0.7907. The value of the coefficient of determination (R2) is 0.7907, meaning that the variance of the dependent variable can be explained by the independent variable of 79.07% percent. Conclusion. the analysis show that the average of beef cattle is 137,342 heads and the average production is 34,083,357 kg over the last 10 years.